(untitled) (Revista BOEM, 2025)
In this article, we explore the main forms of explanation that, in our research, we have identified in classrooms, more specifically, in public school mathematics classes. This work is essentially based on the concerns that emerged during teaching practices, experienced in teaching internships, and in the analysis of these experiences through the study of Jacques Rancière and Gilles Deleuze’s work. Thus, this paper refers to the possibilities of the teaching profession and the attention of teachers and students, especially in attempts of non-explanation movements, as in the financial mathematics teaching activity brought as an example. In this context, the analyses understand that explanation and its forms, even if linked to repetition and regression to infinity, are essential to learning, although they are not sufficient for genuine learning. A learning that is made possible by encounters with worlds of signs and potentiated in the attention to the gaps in the explanation itself.